IMPLIKASI PEMBELAJARAN DI SEKOLAH TERHADAP KEPRIBADIAN ANAK DI MASYARAKAT - Kirana Kirana (Cross-border, 2022)
Learners have now interacted a lot with sources of information and learning messages, along with the rapid developments in the era of globalization, technology and information. Sources of information for students in learning activities that are difficult to control affect the culture, ethics and morals of individuals or society. The low trust attitude of students today is a form of negative influence from cultural and technological developments. Therefore, education needs to evaluate this because if we ignore this, we can be sure that our country will become a country that is destroyed for its community resources. Teachers have the task of bringing about changes in students who initially did not know to know from the results of the process of teaching and learning activities as well as the application of positive values, both personally and publicly carried out professionally. Aspects of changes made by teachers to their students of course not only on the cognitive aspects, but also on the affective and psychomotor aspects.